The legal clinics in the human rights protection system - Zaitseva-Kalaur, Inna (Actual problems of law (Aktual'ni problemi pravoznavstva), 2021)
The article analyzes the legal regulation of free legal aid in order to identify tools for training and retraining of future lawyers. The analysis is conducted through the prism of guarantees of equal access of citizens to justice and guarantees of qualifed legal aid. The development of the studied legislation is connected with the state task of ousting the “underground bar” and low-quality legal aid. The main aspect of its improvement the author calls the conceptual development of the conceptual apparatus in two directions: universalization and differentiation. The author considers legal clinics as a tool to change the quality of legal aid and harmonize educational standards with professional ones.The purpose of this scientifc article is to conduct a comprehensive analysis of the place of legal clinics in the system of human rights protection.The author concludes that in order to improve the quality of education of specialists of legal clinics and improve customer service, legal clinics should:- expand cooperation between legal clinics, regulate the practical activities of legal clinics, develop training materials and raise funds for clinical legal education in Ukraine;- standardize the requirements for teaching and learning plans in order to develop a single set of guidelines and training standards for teachers and students.- develop and sign general ethics commitments for legal clinics;- prepare special clinical projects on criminal cases, in universities, where qualifed lawyers perform the functions of teachers, staff and teach students;- make sure that each clinic has a full-time practicing lawyer, or hire at least one licensed practicing lawyer specializing in criminal cases;- to involve valuable and motivated students who need to go through a rigorous screening process to enter a legal clinic;- to make participation in the work of the legal clinic a component of the educational process, with a mandatory assessment of the level of practical knowledge;- hold weekly meetings for all students and faculty working in legal clinics to discuss ethical and other issues that arise in the feld of client counseling.